The role of meaningful work and workplace attachment styles in predicting entrepreneurial well-being: insights from a structured sales network - Koša, Vladimír; Lisá, Elena (Frontiers in Psychology, 2025)
IntroductionThe study explores how meaningful work (MW) and workplace attachment styles, secure (SE), anxious (AX), and avoidant (AV), predict entrepreneurial well-being within a structured sales network of a financial services firm. It further examines the moderating role of attachment styles and the contextual influence of regional leadership and team financial performance.MethodsData were collected from 300 entrepreneurs using the Work and Meaning Inventory (WAMI), the Workplace Attachment Questionnaire (WAQ), and the Well-Being Index (WHO-5).ResultsRegression analyses show that MW is a robust and consistent predictor of well-being, even after controlling for team-level sales performance and gender. AX initially appeared to amplify the positive relationship between MW and well-being, but this interaction effect diminished once objective financial performance metrics were included. SE to leaders was positively associated with well-being in psychological models but lost significance in the extended model, suggesting that financial performance may partially mediate its effects. Well-being varied significantly by regional leadership, even after adjusting for sales outcomes.DiscussionThe findings underscore the importance of promoting MW, monitoring leadership impact across regions, and integrating subjective and objective indicators when assessing entrepreneurial well-being.